Wykorzystanie własności funkcji liniowej do badania strategii opcyjnych - Stolorz, Beata (Use of Properties of the Linear Function in the Study of Option Strategies, 2006)
In the paper it was presented how the properties of the linear functions could be used in the study of options. An option can be represented as a function of its profit at expiry. Each complex strategy is a combination of basic strategies. Thus, the function of profit of complex option strategies is a linear combination of function of an income of basic strategies with coeficients that are integral non-negativ numbers. Mathematical analysis of these functions facilitates the evaluation of the application of particular strategies and allows the modification of strategies in such a way as to arrive at the expected profit. The method was presented on the basis of spread option strategies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1117, s. 164-171